2020
DOI: 10.1038/s41598-020-61321-7
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of endotracheal tube twisting in facilitating tube delivery to glottis opening during GlideScope intubation in infants: randomized trial

Abstract: Despite an excellent view of the glottis, technical difficulties with endotracheal tube delivery remains in GlideScope intubation. We evaluated whether a spiral-shape twisted tube can facilitate placement of the tracheal tube tip at the center of glottis opening compared to conventional tube for GlideScope intubation in infants. eighty-six infants were randomly placed in either the conventional tube group (group C) or the twist tube group (group T). In group T, the shaft of the tube was manually twisted into a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Therefore, we hypothesized that additional curvature of ETT tip to the left could ease the targeting of ETT into the glottis and result in faster intubation compared with the standard curve. Our hypothesis was proven right as the time required to approach the glottis could be significantly reduced by approximately 2.4 s. Additionally, we could reduce the total intubation time by approximately 5 s. According to another pediatric study using the GlideScope, optimal angulation of the ETT curve could reduce the intubation time by approximately 3 s 10 . Although it might seem like a small difference, this finding is meaningful in pediatric patients with significant physiologic limits on the safe apnea time.…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…Therefore, we hypothesized that additional curvature of ETT tip to the left could ease the targeting of ETT into the glottis and result in faster intubation compared with the standard curve. Our hypothesis was proven right as the time required to approach the glottis could be significantly reduced by approximately 2.4 s. Additionally, we could reduce the total intubation time by approximately 5 s. According to another pediatric study using the GlideScope, optimal angulation of the ETT curve could reduce the intubation time by approximately 3 s 10 . Although it might seem like a small difference, this finding is meaningful in pediatric patients with significant physiologic limits on the safe apnea time.…”
Section: Discussionmentioning
confidence: 74%
“…This might be due to a technical difficulty in ETT handling during intubation attempt 20 . This difficulty can be overcome using an optimal ETT curve 9,10,21 . An adult study using the GlideScope reported that optimal angulation of ETT could reduce the mean intubation time from 54.4 (28.2) sec to 47.1 (21.2) sec 9 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations